2021
DOI: 10.1021/acs.est.1c00618
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Microbial Colonization of Polystyrene Microbeads on the Toxicological Responses in the Sea Urchin Paracentrotus lividus

Abstract: The sea urchin Paracentrotus lividus (P. lividus) was exposed to either virgin or biofilm-covered polystyrene microbeads (micro-PS, 45 μm) in order to test the effect of microbial colonization on the uptake, biodistribution, and immune response. The biofilm was dominated by bacteria, as detected by scanning electron microscopy and 16S rRNA sequencing. A higher internalization rate of colonized micro-PS inside sea urchins compared to virgin ones was detected, suggesting a role of the plastisphere in the interac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 83 publications
3
15
0
Order By: Relevance
“…Importantly, there was no increase of background fluorescence observed that could be attributed to a potential dye leakage, thus validating our experimental approach. This is in line with other similar leakage control experiments, where a negligible dye leakage was observed even after 48 h (Murano et al, 2021).…”
Section: Resultssupporting
confidence: 93%
“…Importantly, there was no increase of background fluorescence observed that could be attributed to a potential dye leakage, thus validating our experimental approach. This is in line with other similar leakage control experiments, where a negligible dye leakage was observed even after 48 h (Murano et al, 2021).…”
Section: Resultssupporting
confidence: 93%
“…The identical but virgin PMMA-MPs caused no physiological changes in the organisms [110]. PS-MPs (45 µm) coated with bacterial biofilm also accumulated at a faster rate in exposed sea urchins than virgin PS-MPs, causing greater egestion rates, decreased immune cell counts, changes in the antioxidant system, and increased generation of reactive oxygen and nitrogen species [111]. In another study under laboratory conditions, the inclusion of a real-world environmental biofilm enhanced detritivorous amphipods' shredding rate of high-density polyethylene (HDPE) plastics (1 cm); however, it was unclear if the shredded particles were rejected or eaten by the organisms [112].…”
Section: Interactions Of Nps With Microorganisms and Antibiotic-resis...mentioning
confidence: 98%
“…Embryonic development represents an extremely sensitive and delicate stage of life for all living organisms, especially for those with external fertilization, such as sea urchins. Indeed, in the marine ecosystem, sea urchin adults and embryos are constantly exposed to a variety of environmental pressures, including both intrinsic and extrinsic/anthropogenic factors causing oxidative and nitrosative stress [1][2][3][4][5][6][7]. Nevertheless, they have acquired the ability, to some extent, to maintain homeostasis in an adverse environment, through the evolution of a 'chemical defensome', an integrated network of gene families and pathways, involved in the protection and repair from damage [8].…”
Section: Introductionmentioning
confidence: 99%